voorbeeld 2

Rekenregels voor logartimen

Hoofdregel:
$
{}^g\log (x) = y \Leftrightarrow g^y = x
$

Hieruit volgt: $
g^{{}^g\log (x)} = x
$

Daarmee kan je de volgende regels aantonen:

$
\begin{array}{l}
{}^g\log (a) + {}^g\log (b) = {}^g\log (ab) \\
{}^g\log (a) - {}^g\log (b) = {}^g\log (\frac{a}{b}) \\
n \cdot {}^g\log (a) = {}^g\log (a^n ) \\
 {}^g\log (a) = \large\frac{{{}\log (a)}}{{{}\log (g)}} \\
\end{array}
$

Voorbeeld 2

$
\begin{array}{l}
{}^2\log (x - 2) + {}^2\log (x) = 3 \\
{}^2\log (x(x - 2)) = 3 \\
x(x - 2) = 2^3 \\
x^2 - 2x = 8 \\
x^2 - 2x - 8 = 0 \\
(x + 2)(x - 4) = 0 \\
x =-2\,\,(v.n.)\,\,of\,\,x = 4 \\
x = 4 \\
\end{array}
$

©2004-2021 Wiskundeleraar - login